Osteoblastoma and Osteoid Osteoma of the Mandible: Review of the Literature and Report of Two Cases - Taylor Ellingsen; Andrew Nalley; Dolphine Oda; Thomas B. Dodson; Peggy P. Lee (Hindawi Limited, 2022)
Osteoblastoma and osteoid osteoma are rare benign neoplasms of the jaws. We reviewed current literature surrounding the ongoing debate over similarities and differences of osteoblastoma and osteoid osteoma and present two cases. Both cases are well-demarcated mixed radiodensity mandibular lesions with histological features of osteoblastoma. They exhibit, however, distinctly unique and contrasting clinical and imaging characteristics suggesting that the first case is osteoblastoma and the second is osteoid osteoma. The first case of a 37-year-old male presents with a large, expansile lesion at posterior mandible, surrounded by a thick sclerotic band. Unusual features include significant buccal/lingual expansion, extensive new bone apposition, and soft tissue edema in the masseter muscle. This is in contrast to the second case of a much smaller lesion in a 17-year-old male with history of recent third molar extraction in the left posterior mandible. In this case, CT imaging revealed a circular, nonexpansile lesion with a sclerotic border surrounded by a radiolucent rim. Both patients underwent surgical excision of the lesion with extraction of the adjacent tooth. We discuss herein the distinct clinical and imaging features.